2016
DOI: 10.1038/ncomms10463
|View full text |Cite
|
Sign up to set email alerts
|

TRAIP/RNF206 is required for recruitment of RAP80 to sites of DNA damage

Abstract: RAP80 localizes to sites of DNA insults to enhance the DNA-damage responses. Here we identify TRAIP/RNF206 as a novel RAP80-interacting protein and find that TRAIP is necessary for translocation of RAP80 to DNA lesions. Depletion of TRAIP results in impaired accumulation of RAP80 and functional downstream partners, including BRCA1, at DNA lesions. Conversely, accumulation of TRAIP is normal in RAP80-depleted cells, implying that TRAIP acts upstream of RAP80 recruitment to DNA lesions. TRAIP localizes to sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 33 publications
6
33
1
Order By: Relevance
“…The E3 ubiquitin ligase TRAIP counteracts replication stress to maintain genome integrity (Feng et al, 2016; Harley et al, 2016; Hoffmann et al, 2016; Soo Lee et al, 2016), and we recently found that it is bound to replication forks that have stalled at a LacR array (Dewar et al, 2017). We therefore asked whether TRAIP is responsible for CMG unloading from stalled forks in mitosis.…”
Section: Resultsmentioning
confidence: 99%
“…The E3 ubiquitin ligase TRAIP counteracts replication stress to maintain genome integrity (Feng et al, 2016; Harley et al, 2016; Hoffmann et al, 2016; Soo Lee et al, 2016), and we recently found that it is bound to replication forks that have stalled at a LacR array (Dewar et al, 2017). We therefore asked whether TRAIP is responsible for CMG unloading from stalled forks in mitosis.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it can be said the localization of RAP80 is directly dependent on TRIP even in the absence of Deoxy-ribonucleic acid lesions. As such, it can be concluded that TRIP has a controlling function on RAP80 particularly in PML nuclear bodies [2]. The findings from the research revealed that TRIP transports RAP80 from PML nuclear bodies to the locus where the damage had occurred.…”
Section: Trip In Rap80 Signaling Pathwaymentioning
confidence: 77%
“…TRAF members directly interact with the TNFR super-family via their cytoplasmic domains [1]. Cytoplasmic domains of TNFR lack catalytic activity and possess no significant homology to each other or other known proteins [2]. To date, TRAF1-7 has been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, a second pathway for RAP80 recruitment has recently been identified that is independent of RNF8/RNF168 ubiquitylation and SUMOylation. This pathway involves interactions between RAP80 and the protein TRAIP [35]. In response to DNA damage, TRAIP translocates to DSBs in complex with RAP80, where it interacts with the heterodimeric RNF20-RNF40 E3 complex.…”
Section: Rap80 Is Targeted To Dsbs Through Two Independent Pathwaysmentioning
confidence: 99%
“…As with RAP80 UIM and SIM mutant-expressing cells, RAP80 recruitment to DSBs is only partially inhibited in TRAIP-depleted cells. This suggests that optimal targeting and accumulation of RAP80 at DSBs is dependent on both TRAIP and ubiquitin and SUMO binding [35]. …”
Section: Rap80 Is Targeted To Dsbs Through Two Independent Pathwaysmentioning
confidence: 99%